Fifteen new species of the spider genus Pholcus (Araneae: Pholcidae) from Southeast Asia - Dong, Tingting; Zheng, Guo; Yao, Zhiyuan; Li, Shuqiang (Zootaxa, 2016)
Fifteen new species from six species groups of the genus Pholcus Walckenaer, 1805 are described from Southeast Asia: Pholcus hinsonensis sp. nov. (male & female, Thailand) and P. tharnlodensis sp. nov. (male & female, Thailand) from the P. bidentatus species group; P. kottawagamaensis sp. nov. (male & female, Sri Lanka) from the P. ethagala species group; P. cenranaensis sp. nov. (male & female, Indonesia) and P. krachensis sp. nov. (male, Thailand) from the P. gracillimus species group; P. anaiensis sp. nov. (male, Indonesia), P. ballarini sp. nov. (male & female, Thailand), P. gou sp. nov. (male & female, Myanmar), P. wan sp. nov. (male & female, Thailand) and P. zhuchuandiani sp. nov. (male & female, Indonesia) from the P. halabala species group; P. chiangmaiensis sp. nov. (male & female, Thailand) and P. taptaoensis sp. nov. (male & female, Thailand) from the P. quinquenotatus species group; P. kaebyaiensis sp. nov. (male & female, Thailand), P. musensis sp. nov. (male & female, Thailand) and P. songkhonensis sp. nov. (male & female, Thailand) from the P. yichengicus species group.